Optimalisasi Peran Instagram Terhadap Strategi Pemasaran Digital Produk Olahraga - Karuma Hijriansyah, Denaz (Universitas Muhammadiyah Kuningan, 2024)
Social media is a new reality in communication in today's digital era that can be used as a business communication strategy for marketers. Social media has strong roots to be a tool in increasing the growth of a business. The features facilitated by Instagram can be utilized as a digital marketing tool, in this case to trade sports product. These features trigger the emergence of creative ideas to launch brand or product campaigns to promos that can be used by sports product entrepreneurs in an effort to attract as many consumers as possible. The application of sports marketing strategies, especially in utilizing social media platforms such as Instagram, plays an important role. The method used in this study is literature review. Researcher and literature review containing a collection of concepts, definitions, and prepositions are inseparable things. This is because the literature review serves as an intermediary medium to be able to see events systematically through the specification of relationships that exist between variables which then helps researcher see the possibilities of the main topic of study. Researcher came to the conclusion that a social media platform called Instagram is still one of the online channels that has a positive value in sports digital marketing. This is revealed by the data exposure of the number of Instagram users globally and the number of specific users in Indonesia itself. The packaging of all sports product sold, requires the continuation of widespread promotion with more careful use of the role of Instagram features. It is important to prepare the required data on Instagram business accounts that can be observed regularly through the Instagram Insights feature while preparing and uploading attention-grabbing visual content in the form of photos, videos, information about sports product, and building interactions to strengthen relationships between users as business people and their followers using Instagram features such as Feeds, Reels, Stories, and Live as digital marketing tools.